Dorsolateral nigral hyperintensity on 3.0T susceptibility‐weighted imaging in neurodegenerative Parkinsonism. Issue 8 (15th March 2015) - Reiter, Eva; Mueller, Christoph; Pinter, Bernadette; Krismer, Florian; Scherfler, Christoph; Esterhammer, Regina; Kremser, Christian; Schocke, Michael; Wenning, Gregor K.; Poewe, Werner; Seppi, Klaus
Abstract Background Absence of a hyperintense, ovoid area within the dorsolateral border of the otherwise hypointense pars compacta of the substantia nigra (referred to as dorsolateral nigral hyperintensity) on iron‐sensitive high‐field magnetic resonance imaging sequences seems to be a typical finding for patients with Parkinson's disease (PD). Objective This study was undertaken to evaluate the diagnostic value of the dorsolateral nigral hyperintensity in a cohort of patients with neurodegenerative parkinsonism including PD, multiple system atrophy (MSA), and progressive supranuclear palsy (PSP) as well as healthy controls using high‐field susceptibility‐weighted imaging (SWI) at 3.0 Tesla (T). Methods Absence of dorsolateral nigral hyperintensity was assessed on visual inspection of anonymized 3.0T SWI scans in a case‐control study including 148 patients with neurodegenerative parkinsonism (PD: n = 104; MSA: n = 22; PSP: n = 22) and 42 healthy controls. Results Dorsolateral nigral hyperintensity was absent unilaterally in all patients with MSA or PSP, in 83 of 90 patients with PD, but only in one of the healthy controls resulting in an overall correct classification of 95.2% in discriminating neurodegenerative parkinsonism from controls in the per‐protocol analysis. Overall correct classification was 93.2% in the intent‐to‐diagnose analysis, including also SWI scans with poor quality (12.1% of all scans) for nigral evaluation. Conclusion Visual assessment of dorsolateral nigral hyperintensity on high‐field SWI scans may serve as a new simple diagnostic imaging marker for neurodegenerative parkinsonian disorders. © 2015 International Parkinson and Movement Disorder Society